RETRACTED: The peculiarity of the growth and purification of Chlorella sp from mineral substances in the northern collector water of the Bukhara Region - Kobilov A.; Buriyev S. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001